Ararat Revisited. (18th January 2019) - Crane, Jacob
Abstract: This article analyzes Mordecai Manuel Noah's failed attempt to establish Ararat, a Jewish city of refuge, in Western New York in 1825. While this unique colonial project has long been overlooked or dismissed by critics and historians, it has also served as a rich site for Jewish authors to construct narratives of counterfactual history that interrogate notions of diasporic Jewish identity. To understand this fascination with Ararat, I start with a consideration of the elaborate founding ceremony Noah staged in Buffalo, New York, and then trace the complex network of performances and texts surrounding Ararat, including Noah's widely circulated call to settlers: his "Proclamation to the Jews." From there I examine the various responses, both positive and negative, to Noah's project that circulated in newspapers across Europe and the United States. Drawing from critics such as Lloyd Pratt, Svetlana Boym, and Wai Chee Dimock in the field of temporal studies, along with work by Joseph Roach and Elizabeth Maddock Dillon on circum-Atlantic performance, I examine the ways in which Noah's Ararat project and the performances, texts, and images surrounding it offer a unique challenge to and expansion of established narratives of early American Jewish identity. Ultimately I locate Ararat's significance in the way it theorizes modern American Jewishness as a diasporic counterhistory that troubles the binaries that structure our readings of the nineteenth-century Atlantic space: nation and other, colonizer and colonized, local and transatlantic, presence and absence.